Processing implicit control: evidence from reading times - McCourt, Michael; Green, Jeffrey J.; Lau, Ellen; Williams, Alexander (Frontiers in Psychology, 2015)
Sentences such as “The ship was sunk to collect the insurance” exhibit an unusual form of anaphora, implicit control, where neither anaphor nor antecedent is audible. The nonfinite reason clause has an understood subject, PRO, that is anaphoric; here it may be understood as naming the agent of the event of the host clause. Yet since the host is a short passive, this agent is realized by no audible dependent. The putative antecedent to PRO is therefore implicit, which it normally cannot be. What sorts of representations subserve the comprehension of this dependency? Here we present four self-paced reading time studies directed at this question. Previous work showed no processing cost for implicit versus explicit control, and took this to support the view that PRO is linked syntactically to a silent argument in the passive. We challenge this conclusion by reporting that we also find no processing cost for remote implicit control, as in: “The ship was sunk. The reason was to collect the insurance.” Here the dependency crosses two independent sentences, and so cannot, we argue, be mediated by syntax. Our Experiments 1-4 examined the processing of both implicit (short passive) and explicit (active or long passive) control in both local and remote configurations. Experiments 3 and 4 added either “three days ago” or “just in order” to the local conditions, to control for the distance between the passive and infinitival verbs, and for the predictability of the reason clause, respectively. We replicate the finding that implicit control does not impose an additional processing cost. But critically we show that remote control does not impose a processing cost either. Reading times at the reason clause were never slower when control was remote. In fact they were always faster. Thus efficient processing of local implicit control cannot show that implicit control is mediated by syntax; nor, in turn, that there is a silent but grammatically active argument in passives.